2019
DOI: 10.1590/1519-6984.183375
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Clustered Regularly Interspaced Short Palindromic Repeats (CRISPRs) in non-clinical Enterococcus faecalis and Enterococcus faecium strains

Abstract: The fidelity of the genomes is defended by mechanism known as Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) systems. Three Type II CRISPR systems (CRISPR1- cas, CRISPR2 and CRISPR3-cas) have been identified in enterococci isolates from clinical and environmental samples. The aim of this study was to observe the distribution of CRISPR1-cas, CRISPR2 and CRISPR3-cas in non-clinical strains of Enterococcus faecalis and Enterococcus faecium isolates from food and fecal samples, including wild m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…In this study, the prevalence of CRISPR1 was higher in E. faecalis (50.0%) than E. faecium isolates (28.6%) that was similar to Lyons et al 31 In the current study, the frequency of CRISPR-Cas systems was significantly higher in E. faecalis (80.0%) than E. faecium (40.0%). This finding was in line with a previous report by Huescas et al 29 from Brazil, who found that the CRISPR-Cas elements of E. faecalis were detected more often than those of E. faecium in non-clinical samples. However, they reported more and less prevalence of CRISPR2 and CRISPR3-cas in the E. faecalis and E. faecium isolates from food and animal fecal samples than in our study, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, the prevalence of CRISPR1 was higher in E. faecalis (50.0%) than E. faecium isolates (28.6%) that was similar to Lyons et al 31 In the current study, the frequency of CRISPR-Cas systems was significantly higher in E. faecalis (80.0%) than E. faecium (40.0%). This finding was in line with a previous report by Huescas et al 29 from Brazil, who found that the CRISPR-Cas elements of E. faecalis were detected more often than those of E. faecium in non-clinical samples. However, they reported more and less prevalence of CRISPR2 and CRISPR3-cas in the E. faecalis and E. faecium isolates from food and animal fecal samples than in our study, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study by Dos Santos et al, 14 showed a lower frequency rate (51.1%) of CRISPR-Cas in enterococci collected from human and food sources. Using PCR, the frequency of CRISPR2 (55.3%) was higher than CRISPR1 (41.2%) and CRISPR3 (35.3%) in this study which was in line with previous reports by Gholizadeh et al 11 from Iran and Huescas et al 29 from Brazil. In contrast to our results, Dos Santos et al 14 reported CRISPR3 (67.4%) as the most prevalent type in enterococci isolates.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, we found that the presence of orphan CRISPR2(42%) was more in Enterococcus than CRISPR1-Cas (23%) and CRISPR3-Cas (5%), which was similar to Alduhaidhawi. 28 In non-clinical Enterococcus faecium isolates, Huescas et al 29 demonstrated a higher prevalence rate of CRISPR2 and lower frequency of CRISPR1-Cas (5.6%) and CRISPR3-Cas (1.8%) system. In contrast to our study, Palmer et al 30 found that CRISPR2 was present in all Enterococcus faecalis isolates.…”
Section: Discussionmentioning
confidence: 99%
“…This complex array signifies a favorable evolutionary adaptation to a symbiotic lifestyle and reflects a potent ability to resist phage attacks within the sponge’s ecosystem. Interestingly, CRISPR/Cas systems have also been reported from samples of feces in wild marine animals and the deep-sea hagfish gut [ 110 , 111 ].…”
Section: Huge Inventory Of Crispr/cas In the Oceanmentioning
confidence: 99%